Rancang Bangun Aplikasi Visualisasi Pertolongan Pertama Berbasis Mobile Menggunakan Teknologi J2ME - Imad, Khusnul; Sutanto, Teguh; Karsam, Karsam (Jurnal JSIKA, 2012)
First aid is a technical staff in needs to save lives after the accident happened or medical emergency before its being sent to the nearest hospital. It is necessary because the early minutes after the accident is critical for the victiom. Generally, after the accident or medical emergency, the people near the victim directly calls an ambulance or send them to the nearest hospital. The problem is when they’re waiting for the ambulance to come or on the way to the hospital, the victim who is having critical emergency condition needs a basic life support before the medical treatment in the hospital. But, not every people knows how to do the first aid properly. One of the solution to overcome that problem is by making a first aid visual application based on mobile for the general society. This application is used when there’s an accident or medical emergency and can be used as an learning first aid application. And also, it informs the nearest hospital as a reference after the first-aid take place. After the impelementation and evaluation that has been done, this application that has been built are able to inform how to do the first-aid properly when the accident happened or medical emergency and able to use as an learning first-aid application and also, can inform the nearest hospital that can be used as a reference after the first-aid take place.   Keywords : Mobile application, First-aid, J2ME.